Pengaruh sistem monokultur dan tumpangsari antara sayuran dan Crotalaria juncea L. terhadap akumulasi Pb, biomassa, dan hasil tanaman - Yekti Sri Rahayu; Tatik Wardiyati; Moch. Dawam Maghfoer (Fakultas Pertanian Universitas Yudharta Pasuruan, 2021)
Intercropping system that involves planting multispecies between accumulator plants and cultivated plants is a way to improve the phytoextraction of heavy metals in agricultural land simultaneously. However, how the effect of accumulator plants on the growth and yield of cultivated plants has not been widely studied. This study aims to determine the growth and yield of vegetables intercropped with accumulator plants from the legume group, namely Crotalaria juncea L. The study was carried out using a randomized block design with one factor, namely Chinese vegetable monoculture (P1), bean vegetable monoculture (P2), and accumulator plant monoculture. Crotalaria juncea L. (P3), an intercropping system between Chinese cabbage and Crotalaria juncea L. (P4; and an intercropping system of beans and Crotalaria juncea L (P5). The results showed that in Chinese cabbage, monoculture planting produced biomass and crop yields. per plant and per plot was higher than the crops grown by intercropping. In the bean crop, monoculture and intercropping systems did not provide differences in biomass yield and fruit yield per plant and per plot. Crotalaria juncea L, which was grown in monoculture produced plant biomass and the yield of the stove per square is higher gi compared to those planted by intercropping. Crotalaria juncea L. intercropped with Chinese cabbage was able to accumulate more Pb in the roots, while Crotalaria juncea intercropped with chickpeas accumulated higher Pb in the stems. Crotalaria juncea plants grown in monoculture accumulated higher Pb than those intercropped with vegetables, so further research is needed to test the effective removal of Pb using other cropping systems.